2020
DOI: 10.2337/figshare.12273077.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Type 2 diabetes, change in depressive symptoms over time, and cerebral small vessel disease – Longitudinal data of the AGES-Reykjavik Study

Abstract: <b></b><b>Objective: </b>Type 2 diabetes has been associated with depression. However, the underlying pathophysiological mechanisms remain unknown. Cerebral small vessel disease, a consequence of diabetes, may lead to depression. Therefore, we evaluated whether cerebral small vessel disease mediates the association between type 2 diabetes and higher depressive symptoms. <p><b>Research Design and Methods: </b>We used longitudinal data from the population-based Age, Gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…One cross-sectional study found that individuals with type 2 diabetes and depression had wider retinal arterioles than individuals with type 2 diabetes but without depression (101), consistent with an association between depression and early microvascular changes in diabetes. Also, a large recent population-based study found that J o u r n a l P r e -p r o o f individuals with type 2 diabetes had greater increase in depressive symptoms over time, and cerebral small vessel disease partly explained this association (102). Type 2 diabetes and the metabolic syndrome are also associated with accelerated stiffening of large arteries (89), and this may contribute to depression in these individuals (103).…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…One cross-sectional study found that individuals with type 2 diabetes and depression had wider retinal arterioles than individuals with type 2 diabetes but without depression (101), consistent with an association between depression and early microvascular changes in diabetes. Also, a large recent population-based study found that J o u r n a l P r e -p r o o f individuals with type 2 diabetes had greater increase in depressive symptoms over time, and cerebral small vessel disease partly explained this association (102). Type 2 diabetes and the metabolic syndrome are also associated with accelerated stiffening of large arteries (89), and this may contribute to depression in these individuals (103).…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%